Exploring the multifaceted dynamics of flowering time regulation in field crops: Insight and intervention approaches - Naik, Yogesh Dashrath; Bahuguna, Rajeev N.; Garcia-Caparros, Pedro; Zwart, Rebecca S.; Reddy, Sai M. S.; Mir, Reyazul Rouf; Jha, Uday Chand; Fakrudin, B.; Pandey, Manish K.; Challabathula, Dinakar; Sharma, Vinay Kumar; Reddy, Umesh K.; et al. (Wiley, 2025)
The flowering time (FTi) plays a critical role in the reproductive success and yield of various crop species by directly impacting both the quality and quantity of grain yield. Achieving optimal FTi is crucial for maximizing reproductive success and ensuring overall agricultural productivity. While genetic factors undoubtedly influence FTi, photoperiodism and vernalization are recognized as key contributors to the complex physiological processes governing flowering in plants. Identifying candidate genes and pathways associated with FTi is essential for developing genomic interventions and plant breeding to enhance adaptability to diverse environmental conditions. This review highlights the intricate nature of the regulatory mechanisms of flowering and emphasizes the vital importance of precisely regulating FTi to ensure plant adaptability and reproductive success. Special attention is given to essential genes, pathways, and genomic interventions geared toward promoting early flowering, particularly under challenging environmental conditions such as drought, heat, and cold stress as well as other abiotic stresses that occur during the critical flowering stage of major field crops. Moreover, this review explores the significant progress achieved in omics technologies, offering valuable insights and tools for deciphering and regulating FTi. In summary, this review aims to provide a comprehensive understanding of the mechanisms governing FTi, with a particular focus on their crucial role in bolstering yields under adverse environmental conditions to safeguard food security.